The role and diagnostic value of assessing the degree of coronary arteries calcification for predicting the severity of coronary heart disease - A. O. Nykonenko; A. L. Makarenkov; H. S. Pidluzhnyi; A. M. Materukhin (Patologìâ)
Coronary heart disease (CHD) is one of the leading mortality causes. According to the latest guidelines, coronary computed tomography angiography (CCTA) is one of the main non-invasive methods for diagnosis of CHD, which allows for quantification of stenosis severity and the characterization of stenotic lesions.